2019
DOI: 10.1007/s00265-019-2778-5
|View full text |Cite|
|
Sign up to set email alerts
|

Hissing like a snake: bird hisses are similar to snake hisses and prompt similar anxiety behavior in a mammalian model

Abstract: Batesian mimicry refers to a harmless species protecting itself from predators by mimicking a harmful species. A case of acoustic Batesian mimicry has been proposed in the naturalist literature: it is suspected that birds called like a snake when disturbed in their cavities to deter mammalian predators or repel competitors. To evaluate this hypothesis, we first test the assumption that the hissing sound produced by adult females of a wild cavity-nesting species -the blue tit (Cyanistes caeruleus) -is acoustica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Notably, lateralization is not the only factor affecting inhibitory control variability. Various studies have reported covariation between inhibitory control and personality [6], including in zebrafish [13]. In our experiment, a measure of personality (sociability as time spent close to the mirror image) did not correlate with inhibitory control.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Notably, lateralization is not the only factor affecting inhibitory control variability. Various studies have reported covariation between inhibitory control and personality [6], including in zebrafish [13]. In our experiment, a measure of personality (sociability as time spent close to the mirror image) did not correlate with inhibitory control.…”
Section: Discussioncontrasting
confidence: 69%
“…For example, animals may benefit from inhibiting foraging when predators are present [2] or when providing parental care [3]. Evidence from diverse vertebrate taxa suggests that the individuals of the same species can differ in performance in inhibitory control tasks (mammals: [4,5]; birds: [6,7]; teleost fishes: [3,8,9]). One remarkable example comes from a fish, Poecilia reticulata, tested in a laboratory task in which an unreachable prey was presented enclosed in a transparent tube.…”
Section: Introductionmentioning
confidence: 99%
“…Mimics could mimic calls of predators to scare off other predators or competitors. For example, some species of hole-nesting birds produce a snake-like hissing call to drive nest predators away (e.g., Dutour et al. 2020 ).…”
mentioning
confidence: 99%
“…B 375: 20190599 cost of caring is high, and the expected level of paternity is low, selection is expected to favour more suspicious males that reduce their paternal investment with increased risk of extra-pair mating [16,[64][65][66][67][68]. Nevertheless, in some organisms, paternal care has been observed even in these cases [13,14,69]. We propose that microbial evolutionary benefits could contribute to the maintenance of paternal care.…”
Section: Discussionmentioning
confidence: 96%